A seawater-degradable plastic packaging barrel and a preparation method thereof

CN121537762BActive Publication Date: 2026-09-04BEIJING ZHONGKE KELAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202512053929.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-31
Publication Date
2026-09-04
Estimated Expiration
2045-12-31

AI Technical Summary

Technical Problem

[0007]本发明的目的旨在克服现有技术中塑料包装桶难以降解、易造成海洋污染的不足,提供一种环境友好、可在海水环境中降解的包装塑料桶,同时满足在海岸边和远洋船队等场景中对机械性能和内容物相容性的高要求

Benefits of technology

1,本发明通过对海水降解塑料包装桶的制备工艺进行具体设定,通过对具体原料的选取,以及通过母粒化处理、一步熔融改性、表面缓释与内部加速耦合等具体操作,实现了高强度可海水降解塑料包装桶的各应用场景的可能性。先进行各组分的预混母粒之后进行熔融塑化,实现了各物料的分散更加均匀,使用存储更加方便;表面缓释与内部加速耦合即使用调控助剂配方的方式高效得到本发明包装桶产品,并且具备随时在原生产线上进行产品性能调整的灵活性;同时由于本发明产品是在潮湿码头、船只甲板等实际场景中应用的,这些应用场景面临特殊的微环境差异,其底部长期接触高湿度地面、积水或沉积物(由于本发明产品是可海水降解的),同时还需持续承担液体内容物的静水压力载荷,导致底部的材料生物降解速率及力学模量衰减速率显著高于相对干燥通风的桶的顶部区域。通过结合本发明具体原料材质而对应这种“下快上慢”的非均匀老化导致的底部优先溃缩或渗漏的应用场景,而设计了自底向上呈阶梯型或渐变型减薄的壁厚结构,通过将底部壁厚设定为顶端的1.2~1.5倍,在降解高风险区预置了必要的腐蚀裕量与力学补偿,有效抵消了底部过快的材料损耗,拉平了桶体上下两端的功能寿命差异,确保产品在全寿命周期内维持结构完整,并最终实现整桶的同步失效与整体崩解。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure IMAGE_B42CE8C8-0B55-4301-AB74-ED24EF93BAC7
    Figure IMAGE_B42CE8C8-0B55-4301-AB74-ED24EF93BAC7
  • Figure IMAGE_E29A090D-2812-4ED1-B671-4186C817105A
    Figure IMAGE_E29A090D-2812-4ED1-B671-4186C817105A
Patent Text Reader

Abstract

The application discloses a seawater-degradable plastic packaging barrel and a preparation method thereof. Through specific setting of steps and parameters of the preparation method, the possibility of realizing various application scenarios of the high-strength seawater-degradable plastic packaging barrel is realized under the premise of basically not changing the existing production line. Through specific setting of components and contents of raw materials, the obtained packaging barrel can guarantee mechanical properties during use and can realize efficient degradation in the marine environment during abandonment, is suitable for packaging requirements of oil, food, chemicals and other application scenarios, and overall reduces environmental pollution and labor cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer packaging technology, specifically to the preparation and application of a seawater-degradable plastic packaging barrel suitable for coastal areas, ocean-going fleets, and research stations, and particularly to a seawater-degradable plastic packaging barrel and its preparation method. Background Technology

[0002] Plastic packaging drums are widely used in coastal operations, ocean shipping, and port storage due to their advantages such as light weight, corrosion resistance, and low cost. They are commonly used to hold food, fresh water, oil, and various chemicals. However, traditional plastic packaging drums are mostly made of non-degradable petroleum-based plastics such as polyethylene (PE) and polypropylene (PP). If discarded and released into the marine environment, they will persist under natural conditions for a long time and gradually break down into microplastics, posing a serious threat to marine ecosystems and biosecurity. Although physical or chemical recycling methods can partially alleviate environmental pressure, the recycling process involves collection, sorting, cleaning, and reprocessing, which is energy-intensive, economically inefficient, and has low recycling efficiency in the dispersed marine environment, making large-scale processing difficult.

[0003] In recent years, biodegradable plastics such as polylactic acid (PLA), polyhydroxyalkanoates (PHA), and polybutylene adipate / terephthalate (PBAT) have shown good degradation performance under industrial composting conditions. However, the marine environment, characterized by low temperature, high salinity, low microbial activity, and fluctuating hydrological conditions, significantly reduces the degradation rate of these materials in seawater.

[0004] Chinese invention patent publication CN114773808A discloses a polylactic acid (PLA) composite degradable material, which improves PLA's degradation performance by modifying PLA. However, in seawater immersion experiments, the material's weight loss and mechanical properties decline slowly, failing to meet the requirements for rapid degradation in marine environments. Chinese invention patent publication CN120958082A discloses a biodegradable resin composition, a biodegradable membrane using the same, and a method for preparing the same. This involves mixing PLA and PHA to obtain a biodegradable resin composition and product with biodegradability and biocompatibility. However, this technical solution has a degradation cycle exceeding 24 months in seawater, and the material's mechanical strength decreases rapidly in a wet state, failing to meet the strength, sealing, and resistance to corrosion requirements of packaging containers.

[0005] In addition, some studies focus on improving the degradation rate of biodegradable plastics in seawater, but often at the expense of mechanical and barrier properties. Chinese invention patent publication CN114106534A discloses a PLA / PHA heat-resistant straw and its preparation method. Through pre-crystallization design, the PLA / PHA plastic straw has a preliminary perfect crystal structure and high crystallinity and heat resistance before entering the high-temperature crystallization water tank. However, this technical solution is not suitable for use as a packaging barrel in seawater. Its tensile strength is low and its barrier properties against oils and chemical solvents are poor, which cannot meet the requirements of impact resistance, stacking and compatibility of contents of the packaging barrel during storage and transportation.

[0006] Therefore, current technologies still lack a plastic material for packaging drums that can simultaneously achieve degradation performance in seawater environments, good mechanical strength (such as impact resistance, pressure resistance, and sealing performance), and compatibility with common contents (such as freshwater, oil, and chemicals). Developing such materials to enable packaging drums to degrade efficiently and harmlessly in the marine environment after completing their service life has become an important technological direction for solving marine plastic pollution and promoting the sustainable development of the marine economy. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of existing plastic packaging drums, such as their difficulty in degradation and their tendency to cause marine pollution. It aims to provide an environmentally friendly plastic packaging drum that can degrade in seawater, while simultaneously meeting the high requirements for mechanical performance and compatibility with contents in scenarios such as coastal areas and ocean-going fleets. This invention, through optimized material formulation, modified additive combinations, and structural design, aims to achieve the following objectives: reduce marine plastic pollution and protect the marine ecological environment; and provide an environmentally friendly and sustainable packaging solution for related industries.

[0008] The technical solution of the present invention is achieved through the following technical means: A seawater-degradable plastic packaging bucket, wherein the thickness of the bottom wall of the bucket is 1.2 to 1.5 times the thickness of the top wall, and the thickness of the wall gradually decreases from the bottom to the top in a stepped or gradual manner; and the material of the seawater-degradable plastic packaging bucket contains, by weight percentage: biodegradable resin base: 85 to 95 wt.%; non-enzymatic seawater degradation promoter: 1 to 5 wt.%; enzymatic seawater degradation promoter: 1 to 5 wt.%; surface hydrolysis inhibitor: 0.5 to 5 wt.%.

[0009] Preferably, the average thickness of the barrel wall is 2~10mm.

[0010] Preferably, the biodegradable resin substrate is one or more of polybutylene succinate, polyesteramide, polybutylene succinate-lactic acid copolymer, or polylactic acid.

[0011] Preferably, the non-enzymatic seawater degradation promoter is one or more of calcium oxide, calcium hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, or calcium sulfate.

[0012] Preferably, the enzymatic seawater degradation promoter is one or more of alginate oligosaccharides, poly-γ-glutamic acid, sodium alginate, cellulose, lignin, chitin, fructose, or whey protein powder.

[0013] Preferably, the surface hydrolysis inhibitor is polyethylene wax.

[0014] Preferably, the non-enzymatic seawater degradation promoter is calcium hydroxide and / or calcium carbonate.

[0015] Preferably, the seawater biodegradable plastic packaging barrel also includes one or more of the following additives: flow promoter, plasticizer, compatibilizer, heat stabilizer, flame retardant, antistatic agent, conductive agent or rodent repellent: 0.1~10wt.%.

[0016] A method for preparing a seawater-degradable plastic packaging bucket, wherein the prepared seawater-degradable plastic packaging bucket is the seawater-degradable plastic packaging bucket described above. Includes the following steps: (1) Preparation of materials: Prepare materials according to the following formula: biodegradable resin base: 85~95 parts by weight; non-enzymatic seawater degradation promoter: 1~5 parts by weight; enzymatic seawater degradation promoter: 1~5 parts by weight; surface hydrolysis inhibitor: 0.5~5 parts by weight.

[0017] (2) Masterbatch preparation: The non-enzymatic seawater degradation promoter, enzymatic seawater degradation promoter, surface hydrolysis inhibitor and 30~70wt.% of the biodegradable resin base obtained in step (1) are dried respectively. After drying, they are mixed in a mixer to obtain a premix. The premix is ​​then added to a twin-screw extruder for extrusion. The temperature is set to 165~185℃ and the screw speed is 150~300rpm. After the extruded melt is cooled in a water bath, it is pelletized to obtain uniform masterbatch.

[0018] (3) Melting and plasticizing: The masterbatch obtained in step (2) is uniformly mixed with the remaining biodegradable resin base prepared in step (1), and the whole mixture is placed in an injection molding machine for heating and melting. The barrel temperature is 155~220℃ and the die head temperature is 175~195℃.

[0019] (4) Injection molding: The mold temperature is preheated to 20~25℃, and the molten material after melting and plasticizing in step (3) is injected into the mold. Injection molding is carried out under the conditions of injection pressure of 120~140 Bar and holding pressure of 90~120 Bar.

[0020] (5) Cooling and demolding: After injection molding in step (4), the mold is cooled for 14 to 20 seconds and then demolded to obtain the seawater biodegradable plastic packaging barrel.

[0021] Preferably, in step (2), the drying is performed under vacuum at 60~80°C until the moisture content in the material is less than 300ppm.

[0022] Preferably, the mixing in the mixer in step (2) specifically means mixing in the mixer at room temperature and pressure for 8 to 13 minutes.

[0023] Preferably, the injection speed in step (4) is set to 60~80mm / s.

[0024] The technical advantages of this invention are as follows: 1. This invention, through specific design of the preparation process for seawater-degradable plastic packaging barrels, and by selecting specific raw materials and implementing specific operations such as masterbatch processing, one-step melt modification, and surface slow release coupled with internal acceleration, realizes the possibilities of various application scenarios for high-strength seawater-degradable plastic packaging barrels. Premixing the components into masterbatch before melt plasticization achieves more uniform dispersion of the materials, making them more convenient to use and store. Surface slow release coupled with internal acceleration, achieved by using a controlled additive formulation, efficiently yields the packaging barrel product of this invention, and provides the flexibility to adjust product performance on the original production line at any time. Furthermore, since the product of this invention is used in actual scenarios such as wet docks and ship decks, these application scenarios face unique microenvironmental differences. The bottom of the barrel is in long-term contact with high-humidity ground, water, or sediment (because the product of this invention is seawater-degradable), and must also continuously bear the hydrostatic pressure load of the liquid contents. This results in a significantly higher rate of biodegradation and mechanical modulus decay at the bottom than in the relatively dry and ventilated top area of ​​the barrel. By combining the specific raw materials of this invention with the application scenario of non-uniform aging ("fast at the bottom and slow at the top") leading to preferential collapse or leakage at the bottom, a wall thickness structure with a stepped or gradually thinning shape from bottom to top is designed. By setting the bottom wall thickness to 1.2 to 1.5 times that of the top, necessary corrosion margin and mechanical compensation are pre-set in the high-risk degradation zone, effectively offsetting the excessively rapid material loss at the bottom, leveling the functional lifespan difference between the upper and lower ends of the barrel, ensuring that the product maintains structural integrity throughout its entire life cycle, and ultimately achieving synchronous failure and overall disintegration of the entire barrel.

[0025] 2. This invention, by specifically defining the components and content of each component in the packaging barrel material, rationally sets the components and content of the biodegradable resin base, non-enzymatic seawater degradation promoter, enzymatic seawater degradation promoter, and surface hydrolysis inhibitor. This results in a seawater-degradable packaging barrel with mechanical properties such as strength and fracture toughness (maximum load, tensile strength, tensile modulus of elasticity, elongation at break, heat distortion temperature, 9-month storage tensile strength retention rate, and 9-month storage elongation at break retention rate) that meet the performance requirements of the packaging barrel, and also has an efficient and controllable degradation time window. It achieves a balance between mechanical strength, temperature resistance, compatibility with contents, and seawater degradability, ensuring performance during use and achieving efficient degradation in the marine environment when discarded. It is suitable for packaging needs in application scenarios such as oil, food, and chemicals, reducing environmental pollution and labor costs. Detailed Implementation

[0026] Example 1 This embodiment illustrates a method for preparing a 20L seawater-degradable plastic oil drum as defined in this invention, comprising the following steps: (1) Preparation of materials: The materials are prepared according to the following formula: biodegradable resin: polybutylene succinate PBS 92 parts by weight, non-enzymatic degradation promoter: calcium carbonate 3 parts by weight, enzymatic degradation promoter: cellulose 2 parts by weight, surface degradation inhibitor: polyethylene wax 1 part by weight, flow promoter (AZ) 2 parts by weight, rodent repellent (capsaicin) 0.2 parts by weight, flame retardant (TEHP) 0.4 parts by weight.

[0027] (2) Masterbatch preparation: 50% of the PBS resin obtained in step (1) and all of the calcium carbonate, cellulose, polyethylene wax and other additives (AZ, capsaicin, TEHP) were vacuum dried at 80°C until the moisture content was less than 300 ppm. The dried materials were then mixed and dry-mixed in a high-speed mixer at 600 rpm for 8 minutes until macroscopically uniform. The premixed materials were added to a co-rotating twin-screw extruder, with the temperature set at 140°C, the melt temperature maintained at 150°C, and the screw speed at 250 rpm. After the extruded melt was cooled in a water bath, it was pelletized to obtain uniform masterbatch.

[0028] (3) Melt plasticizing: The obtained masterbatch is mixed evenly with the remaining PBS resin, and then placed in an injection molding machine and heated to melt. Melt plasticizing is carried out under the condition of barrel temperature of 210℃.

[0029] (4) Injection molding: The mold temperature is preheated to 25°C. The molten material after melting and plasticizing in step (3) is injected into the mold. The injection pressure is 140 bar, the holding pressure is 100 bar, the injection speed is 65 mm / s, the cooling time is 14 s, and the holding time is 2s.

[0030] (5) Cooling and demolding: The product temperature is reduced to room temperature, and then demolded to obtain the seawater biodegradable plastic packaging bucket. The average wall thickness of the bucket prepared in this embodiment is 4 mm, and the bottom thickness is 6 mm.

[0031] The maximum load, tensile strength, tensile modulus of elasticity, elongation at break, heat distortion temperature, 9-month storage tensile strength retention rate, 9-month storage elongation at break retention rate, 30-day seawater weight loss, 90-day seawater weight loss, and 360-day seawater weight loss of this embodiment were tested, and the results are shown in Table 1 and Table 2.

[0032] Example 2 This embodiment illustrates implementation methods with different components. In this embodiment, PBS is replaced with PBSL30 (the copolymer contains 30% lactic acid by molar mass), and the weight ratio of PBSL30:calcium carbonate:cellulose:polyethylene wax is 92:3:2:1, with the rest remaining unchanged. The remaining steps are the same as in Example 1. The various indicators of the product obtained in this embodiment were tested, and the results are shown in Tables 1 and 2.

[0033] Example 3 This embodiment illustrates the implementation of different components. In this embodiment, calcium carbonate is replaced with calcium oxide, and the weight ratio of PBS:calcium oxide:cellulose:polyethylene wax is 92:3:2:1, while the rest remains unchanged. The remaining steps are the same as in Example 1. The various indicators of the product obtained in this embodiment were tested, and the results are shown in Tables 1 and 2.

[0034] Example 4 This embodiment illustrates the implementation of different components. In this embodiment, cellulose is replaced with poly-γ-glutamic acid, and the weight ratio of PBS:calcium carbonate:poly-γ-glutamic acid:polyethylene wax is 92:3:2:1, while the rest remains unchanged. The remaining steps are the same as in Example 1. The various indicators of the product obtained in this embodiment were tested, and the results are shown in Tables 1 and 2.

[0035] Example 5 This embodiment illustrates the implementation of different components. The proportions are adjusted, with the weight ratio of PBS:calcium carbonate:cellulose:polyethylene wax being 92:4:1:1, while the rest remain unchanged. The remaining steps are the same as in Example 1. The product obtained in this embodiment was tested for various indicators, and the results are shown in Tables 1 and 2.

[0036] Example 6 This embodiment illustrates the implementation of different components. The proportions are adjusted, with the weight ratio of PBS:calcium carbonate:cellulose:polyethylene wax being 92:1:4:1, while the rest remain unchanged. The remaining steps are the same as in Example 1. The product obtained in this embodiment was tested for various indicators, and the results are shown in Tables 1 and 2.

[0037] Comparative Example 1 This comparative example illustrates a comparative test performed without adhering to the component settings of this invention. Compared to Example 1, this comparative example omits the non-enzymatic seawater degradation promoter, the enzymatic seawater degradation promoter, and the surface hydrolysis inhibitor, replacing their weight parts with an equal weight part of a biodegradable resin substrate PBS. All other aspects remain unchanged, and the remaining steps are identical to those in Example 1. The various indicators of the product obtained in this comparative example were tested, and the results are shown in Table 1.

[0038] Comparative Example 2 This comparative example is used to illustrate a comparative test where the components are not set according to the present invention. Compared to Example 1, this comparative example omits the non-enzymatic seawater degradation promoter calcium carbonate, i.e., the ratio of PBS:cellulose:polyethylene wax is 92:4:1, while all other components remain unchanged. The remaining steps are the same as in Example 1. The various indicators of the product obtained in this comparative example were tested, and the results are shown in Table 1.

[0039] Comparative Example 3 This comparative example is used to illustrate a comparative test where the components are not set according to the present invention. Compared with Example 1, this comparative example removes the enzymatic seawater degradation promoter cellulose and adjusts the ratio of PBS:calcium carbonate:polyethylene wax to 92:5:1, while keeping the rest unchanged. The remaining steps are the same as those in Example 1. The various indicators of the product obtained in this comparative example were tested, and the results are shown in Table 1.

[0040] Comparative Example 4 This comparative example is used to illustrate a comparative test where the components are not set according to the present invention. Compared with Example 1, this comparative example removes the surface hydrolysis inhibitor polyethylene wax and adjusts the ratio of PBS:calcium carbonate:cellulose to 92:3:2, while keeping the rest unchanged. The remaining steps are the same as those in Example 1. The various indicators of the product obtained in this comparative example were tested, and the results are shown in Table 1.

[0041] Comparative Example 5 This comparative example is used to illustrate a comparative test that does not follow the content settings of the present invention. Compared with Example 1, this comparative example reduces the proportions of non-enzymatic seawater degradation promoter and enzymatic seawater degradation promoter, meaning that both and their sum are outside the numerical range set by the present invention (the ratio is supplemented using PBS). Specifically, the ratio of PBS:calcium carbonate:cellulose:polyethylene wax is 96:0.5:0.5:1, while the rest remains unchanged. The remaining steps are the same as those in Example 1. The various indicators of the product obtained from this comparative example were tested, and the results are shown in Tables 1 and 2.

[0042] Comparative Example 6 This comparative example is used to illustrate a comparative test that does not follow the content settings of this invention. Compared with Example 1, this comparative example increases the proportion of non-enzymatic seawater degradation promoter (excess amount is reduced and made up with PBS), that is, PBS:calcium carbonate:cellulose:polyethylene wax is 87:6:4:1, and the rest remain unchanged. The remaining steps are the same as those in Example 1. The various indicators of the product obtained from this comparative example were tested, and the results are shown in Table 1.

[0043] Comparative Example 7 This comparative example is used to illustrate a comparative test that does not follow the content settings of the present invention. Compared with Example 1, this comparative example increases the proportion of surface hydrolysis inhibitor to 8 wt.% (the excess was reduced and made up using PBS), that is, PBS:calcium carbonate:cellulose:polyethylene wax is 85:3:2:8, and the rest remains unchanged. The remaining steps are the same as those in Example 1. The various indicators of the product obtained from this comparative example were tested, and the results are shown in Tables 1 and 2.

[0044] For the mechanical property testing of each embodiment and comparative example, tensile strength, flexural strength and elongation at break were tested in accordance with the standard GB / T 1040.2-2022.

[0045] For heat resistance, the heat distortion temperature test is used.

[0046] For the humid environment storage performance test, the storage was carried out at 25 degrees and 70% humidity for 9 months to test the retention rate of tensile strength and elongation at break.

[0047] For the seawater degradation performance testing, the samples were immersed in artificial seawater, and the mass loss rate of the test materials was measured after specific time intervals (30 days, 90 days, and 360 days). The results are shown in Tables 1 and 2. Table 1 is a data table of the material mechanical property test results for each embodiment and comparative example; Table 2 is a data table of the seawater degradation test results for each embodiment and comparative example.

[0048] Table 1 As can be seen from Table 1, compared with Comparative Examples 1-7, Examples 1 to 6 of the present invention successfully prepared a series of modified materials. The materials obtained in Examples 1 to 6 met expectations in terms of mechanical properties and thermal stability (heat distortion temperature ≥ 85℃) and in storage resistance tests at 25 degrees Celsius and 70% humidity. It can be seen that although Comparative Example 6 has a relatively high maximum load, considering the overall performance, its increased proportion of non-enzymatic seawater degradation accelerator resulted in unsatisfactory retention rates of tensile strength and elongation at break after 9 months of storage. This is because the excessive addition of non-enzymatic seawater degradation accelerator worsens the long-term storage performance stability. Comparative Example 1, lacking non-enzymatic seawater degradation accelerator, enzymatic seawater degradation accelerator, and surface hydrolysis inhibitor, also failed to meet requirements for tensile modulus of elasticity, elongation at break, heat distortion temperature, and retention rates of tensile strength and elongation at break after 9 months of storage. Other comparative examples had one or more indicators that did not meet the requirements, but all indicators in Examples 1 to 6 met the requirements. This indicates that the present invention, by specifically defining the specific components and their content, can meet the application requirements for seawater-degradable plastic packaging barrels, and its preparation method can obtain seawater-degradable plastic packaging barrels that meet the requirements.

[0049] Furthermore, as shown in Table 1, Examples 2, 3, and 4 effectively adjusted the mechanical properties of the materials by changing the specific components of the biodegradable resin substrate, the non-enzymatic seawater degradation accelerator, and the enzymatic seawater degradation accelerator. This demonstrates that the specific components can be reasonably adjusted according to specific application scenarios. Examples 5 and 6 show that mechanical and storage properties can be optimized simply by adjusting the ratio of the non-enzymatic seawater degradation accelerator and the enzymatic seawater degradation accelerator. Comparative Examples 2, 3, and 4, however, removed the non-enzymatic seawater degradation accelerator, the enzymatic seawater degradation accelerator, and the surface hydrolysis inhibitor, respectively. Table 1 shows that their indicators did not meet the requirements, proving that the present invention is not merely a specific setting and modification of the biodegradable resin substrate, but rather a holistic approach that specifically sets and coordinates the various components, resulting in a close synergistic effect between them. This verifies the necessity of the non-enzymatic seawater degradation accelerator, the enzymatic seawater degradation accelerator, and the surface hydrolysis inhibitor.

[0050] Comparative Examples 5 and 6 investigated the effects of insufficient and excessive content of hydrolysis accelerators (the total amount of non-enzymatic seawater degradation accelerators and enzymatic seawater degradation accelerators). As shown in Table 1, the total amount cannot be too high or too low; otherwise, the various indicators cannot be fully met. This also proves that the content of each component set in this invention is optimal. Moreover, this setting is not based on the individual performance of each component. There is no evidence in the prior art that the total amount of non-enzymatic seawater degradation accelerators and enzymatic seawater degradation accelerators has a significant impact on the elongation at break. It is generally believed that the increase of accelerators will accelerate material degradation and eventually lead to a decrease in the elongation at break. There is no prior art showing that reducing their content will reduce the elongation at break. That is, the specific content limits of each component in this invention do not act independently but have a closely coordinated effect.

[0051] Further, examples and comparative examples (Examples 1-6, Comparative Example 5, and Comparative Example 7) with heat distortion temperature greater than 85 degrees, tensile strength retention rate greater than 75% after 9 months of storage, and elongation at break greater than 60% were selected for packaging barrel functional testing. Seawater degradation was performed after 30, 90, and 300 days, and the results are shown in Table 2.

[0052] Table 2 As can be seen from Table 2, the degradation rates of all embodiments of the present invention are qualified, especially the 360-day seawater weight loss of all embodiments reaches 100%. Although Comparative Example 7 is merely a comparative test with an excessive amount of surface hydrolysis inhibitor, and its mechanical properties are basically qualified, its degradation rate is greatly reduced, especially the 360-day seawater weight loss is only 51%. Comparative Example 5 is also greatly reduced in degradation rate simply by reducing the ratio of non-enzymatic seawater degradation promoter and enzymatic seawater degradation promoter. This proves that the specific setting of the content of each component in the present invention is the most reasonable content setting creatively set, thus emphasizing the key of appropriate ratio to material performance.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a seawater-degradable plastic packaging bucket, characterized in that, Includes the following steps: (1) Preparation of materials: Prepare materials according to the following formula: biodegradable resin base: 85~95 parts by weight; non-enzymatic seawater degradation promoter: 1~5 parts by weight; enzymatic seawater degradation promoter: 1~5 parts by weight; surface hydrolysis inhibitor: 0.5~5 parts by weight. The biodegradable resin substrate is one or more of polybutylene succinate, polyesteramide, or polybutylene succinate-lactic acid copolymer; The non-enzymatic seawater degradation promoter is one or more of the following: alginate oligosaccharide, poly-γ-glutamic acid, sodium alginate, calcium oxide, calcium hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, or calcium sulfate. The enzymatic seawater degradation promoter is one or more of cellulose, lignin, chitin, sucrose, fructose, or whey protein powder; (2) Masterbatch preparation: The non-enzymatic seawater degradation promoter, enzymatic seawater degradation promoter, surface hydrolysis inhibitor and 30~70wt.% of the biodegradable resin base obtained in step (1) are dried respectively. After drying, they are mixed in a mixer to obtain a premix. The premix is ​​then added to a twin-screw extruder for extrusion. The temperature is set to 165~185℃ and the screw speed is 150~300rpm. After the extruded melt is cooled in a water bath, it is pelletized to obtain uniform masterbatch. (3) Melting and plasticizing: The masterbatch obtained in step (2) is uniformly mixed with the remaining biodegradable resin base prepared in step (1), and the whole mixture is placed in an injection molding machine for heating and melting. The barrel temperature is 155~220℃ and the die head temperature is 175~195℃. (4) Injection molding: The mold temperature is preheated to 20~25℃, and the molten material after melting and plasticizing in step (3) is injected into the mold. Injection molding is carried out under the conditions of injection pressure of 120~140 Bar, injection speed of 60~80 mm / s, and holding pressure of 90~120 Bar. (5) Cooling and demolding: After injection molding in step (4), the mold is cooled for 14-20 seconds and then demolded to obtain the seawater biodegradable plastic packaging bucket; The thickness of the bottom wall of the seawater biodegradable plastic packaging barrel is 1.2 to 1.5 times that of the top wall, and the thickness of the barrel wall gradually decreases from the bottom to the top in a stepped or gradual manner; the average thickness of the barrel wall is 2 to 10 mm; and the material of the seawater biodegradable plastic packaging barrel contains, by weight percentage: biodegradable resin base: 85 to 95 wt%; non-enzymatic seawater degradation promoter: 1 to 5 wt%; enzymatic seawater degradation promoter: 1 to 5 wt%; surface hydrolysis inhibitor: 0.5 to 5 wt%.

2. The preparation method according to claim 1, characterized in that, The surface hydrolysis inhibitor is polyethylene wax.

3. The preparation method according to claim 1, characterized in that, The non-enzymatic seawater degradation promoter is calcium hydroxide and / or calcium carbonate.

4. The preparation method according to claim 1, characterized in that, The seawater biodegradable plastic packaging barrel also includes one or more of the following additives: flow promoter, plasticizer, compatibilizer, heat stabilizer, flame retardant, antistatic agent, conductive agent or rodent repellent: 0.1~10wt.%.

5. The preparation method according to claim 1, characterized in that, In step (2), the drying is carried out under vacuum at 60~80℃ until the moisture content in the material is less than 300ppm.

6. The preparation method according to claim 1 or 5, characterized in that, The mixing in the mixer mentioned in step (2) specifically refers to mixing the materials in the mixer at room temperature and pressure for 8 to 13 minutes.

Citation Information

Patent Citations

  • PLA / PHA heat-resistant straw and preparation method thereof

    CN114106534A

  • Polylactic acid composite degradable material

    CN114773808A

  • Biodegradable resin composition, biodegradable film using the same, and method for preparing the same

    CN120958082A

  • Controllable oxidative-biological degradation plastic master batch and preparation method thereof

    CN104031302A

  • Environment-friendly degradable packaging composite film and preparation method thereof

    CN109988400A